Life cycle and survivorship of eri silkworm, Samia cynthia ricini biosduval (Lepidoptera: Saturniidae) on three different cassava leaves diet - Nurkomar, Ihsan; Dina Wahyu Trisnawati; Arrasyid, Fiber (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Samia cynthia ricini, Eri silk worm is an oligophagous insect that consume several plant leaves, including cassava. However, it is not sure whether all cassava leaves can be used as a diet for S. cynthia ricini. This research was conducted to study the life cycle and survivorship of S. cynthia ricini, which was given three kinds of Manihot spp. leaves diet i.e., Manihot glaziovii, M. esculenta, and M. utilissima. The research was conducted by rearing silkworms in these three kinds of leaves diet. The development time of each stage, pupa and cocoon shell weight, and daily fecundity of adult of S. cynthia ricini were observed in this research. The results showed that S. cynthia ricini completed their life cycle when fed on M. glaziovii and M. esculenta leaves diet only. There was no difference in the development time of larvae when fed on M. glaziovii (28.15 days) and M. esculenta (28.19 days) leaves diet. However, the development times of pupae (17.99 and 18.21 days) and adult (3.96 and 3.62 days) of S. cynthia ricini were different when fed on M. glaziovii and M. esculenta leaves diet, respectively. The weight of S. cynthia ricini cocoon shell fed on M. esculenta (0.42 g) leaves diet was heavier than M. glaziovii (0.35 g), but the pupal weight of S. cynthia ricini was heavier when fed on M. glaziovii (1.90 g) than M. esculenta (1.77 g) leaves diet. There was no difference in adult fecundity among the two leaves diet tested. Adult of S. cynthia ricini produced 1214.89 eggs when the larvae reared on M. glaziovii and 1150.30 eggs on M. esculenta. We concluded that M. esculenta is the best alternate diet source for S. cynthia ricini.